Modeling activity diagram to colored petri net for validation and verification based on non functional parameters - Balagatabi, Hossein Nematzadeh (2008)
UML is one of the modeling tools which gains wide area of usage in developing softwares. It consists of many diagrams which help developers of a software to produce better product. One of its diagrams is called Activity Diagram. It is a deliverable which is usually produced in the analysis phase of software. It consists of many important benefits, yet it has weaknesses too. One important thing which the current Activity Diagram is unable to do it is that it can not be validated and verified. The current Activity Diagram is a functional diagram and to extract non functional parameters from functional diagram is impossible but through modeling it to colored Petri net and by using the formalism of colored Petri net we may able to verify and validate the Activity Diagram. The ultimate outcome of this study would be handful information to manage the current mentioned Activity Diagram's weakness. Moreover a computer tool is provided called ADET to validate and verify the activity diagram.